Urokinase system expression in gastric carcinoma: prognostic impact in an independent patient series and first evidence of predictive value in preoperative biopsy and intestinal metaplasia specimens - Beyer, Bianca C. M.; Heiss, Markus Maria; Simon, Erich-Horst; Gruetzner, Klaus-Uwe; Babic, Rudolf; Jauch, Karl-Walter; Schildberg, Friedrich-Wilhelm; Allgayer, Heike (Cancer, 2006)
Background: The prognostic relevance of urokinase-type plasminogen activator (u-PA), u-PA receptor (u-PAR), and plasminogen activator inhibitor 1 (PAI-1) in gastric carcinoma was demonstrated in an independent patient series. To the authors' knowledge,the roles of these activators as predictors of aggressive phenotypes in preoperative biopsies, Helicobacter pylori infection, and intestinal metaplasia have to date not been investigated simultaneously in resected tumors. The objectives of the current study were 1) to demonstrate the prognostic relevance of u-PA, u-PAR, and PAI-1 in an independent series; 2) to evaluate u-PA system expression in preoperative biopsy specimens compared with resected tumors; and 3) to evaluate u-PA system expression in intestinal metaplasias and samples with H. pylori infection. Methods: In 104 patients with gastric carcinoma (median follow-up, 68 mos), u-PA, u-PAR, and PAI-1 in tumors and metaplasias were evaluated immunohistochemically. Preoperative biopsies were evaluated in a subset of patients. Patients were screened for H. pylori (urease) and tumor cells in bone marrow (u-PAR/CK18). Results: u-PA and PAI-1 were confirmed as independent prognostic parameters, and u-PAR was associated with a trend toward a poor prognosis. u-PA system tumor expression was found to be correlated significantly with u-PAR in disseminated tumor cells and H. pylori-infected tumors, implicating a role of H. pylori in protease induction. There was a significant correlation noted between u-PA system staining between preoperative biopsies and the results in resected tumors. The expression of u-PAR and PAI-1 in intestinal metaplasias was found to be associated significantly with advanced tumor stage (depth of invasion; pathologic tumor status) and lymph node involvement (pathologic lymph node status) and was correlated significantly with u-PA system expression in tumors. Conclusions: To the author's know the current study is the first to date to demonstrate that u-PA system expression may serve as a predictor of risk in intestinal metaplasias and preoperative biopsies, implicating consequences for neoadjuvant therapy. The independent impact on recurrence and survival and a correlation with u-PAR-expression of minimal residual disease were identified in this independent series.
Gesehen am 02.05.2022